Diferença dos níveis séricos do marcador tumoral CEA em cadelas (Canis lupus familiaris) com alterações mamárias não neoplásicas e neoplasias mamárias - Rabbers, Alice Regina Machado (2019)
CEA antigen is a serum glycoprotein used to monitoring women with breast cancer. The aims of this study were to evaluate the variations of the CEA tumour marker in healthy bitches, with mammary tumors and with non-neoplastic mammary changes, and to determine if these alterations can alter the values of the marker. Consequently, would be possible to verify if the CEA was specific to identify the specificity for mammary neoplastic alterations, contributing to the future use in the staging, monitoring and prognosis of the patients. CEA serum levels were determined in 30 female dogs: 10 healthy ones without any type of mammary alteration (G1 – control); 10 with nonneoplastic mammary changes, such as lactation, pseudopregnancy or mastitis (G2) and 10 bitches with mammary neoplasia (G3). As a result, an average of 0.12 (±0.12) ng/mL in G1 (control), an average of 0.68 (±0.23) ng/mL in G2 and an average of 1.29 (±0.14) ng/mL in G3 was achieved. In the multiple comparisons of averages, the Tukey’s test was used (p<0,05). Through this study, a significant statistical difference was observed in the CEA values between healthy bitches, with mammary alterations and with mammary neoplasia. Base on this, can be concluded that CEA is a marker that can be used for mammary neoplasia in female dogs, however, it may be increased in non-neoplastic mammary changes, lacking a better definition of its reference values.